2015
DOI: 10.1126/science.1259145
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary resurrection of flagellar motility via rewiring of the nitrogen regulation system

Abstract: Step 1 mutations increase intracellular levels of phosphorylated NtrC, a distant 10 homologue of FleQ, which begins to commandeer control of the fleQ regulon at the cost 11 of disrupting nitrogen uptake and assimilation.Step 2 is a switch-of-function mutation 12 that redirects NtrC away from nitrogen uptake and towards its novel function as a 13 flagellar regulator. Our results demonstrate that natural selection can rapidly rewire 14 regulatory networks in very few, repeatable mutational steps. 25Here we moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
114
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(118 citation statements)
references
References 30 publications
2
114
2
Order By: Relevance
“…When presented with environmental challenges, organisms adapt by using a range of strategies, including new enzymatic functions and novel regulatory processes. In natural systems, there are numerous precedents showing that selecting for growth under specified conditions can yield mutations that rewire gene regulation (27)(28)(29)(30)(31). For example, Taylor et al (27) showed that immotile mutants of Pseudomonas fluorescens subjected to selections for motility evolve by repurposing a protein that normally functions in nitrogen uptake toward a new function involving flagellar regulation.…”
Section: Discussionmentioning
confidence: 99%
“…When presented with environmental challenges, organisms adapt by using a range of strategies, including new enzymatic functions and novel regulatory processes. In natural systems, there are numerous precedents showing that selecting for growth under specified conditions can yield mutations that rewire gene regulation (27)(28)(29)(30)(31). For example, Taylor et al (27) showed that immotile mutants of Pseudomonas fluorescens subjected to selections for motility evolve by repurposing a protein that normally functions in nitrogen uptake toward a new function involving flagellar regulation.…”
Section: Discussionmentioning
confidence: 99%
“…If the generated RNA has an adaptive phenotypic effect by matching a target, selection may fix this regulatory pair. In comparison, evolving a new TF may be more difficult (however, see Taylor et al, 2015). Both bacterial sRNAs and eukaryotic miRNAs indeed often show signs of being recently "invented" (Cuperus, Fahlgren, & Carrington, 2011).…”
Section: Why Are Srnas Used Everywhere?mentioning
confidence: 97%
“…Remarkably, bacteria are capable of evolving new functions over a weekend, as shown in a recent study of P. fluorescens where engineered immotile strains re-evolved flagellar motility in v96 h. Starvation on solid agar imposed strong selection for motility in the immotile bacteria which responded by evolutionary rewiring of their nitrogen gene regulatory network, switching its specificity towards regulation of flagellar genes instead, thereby allowing the cells to regain the ability to build flagella and swim towards nutrients (Taylor et al, 2015). My own experimental evolution studies of bacterial populations reveal the potential for similarly rapid evolutionary gain or loss of a wide variety of ecologically important traits, including colony morphology (Brockhurst et al, 2004(Brockhurst et al, , 2005(Brockhurst et al, , 2007bVogwill et al, 2011), biofilm production (Brockhurst et al, 2007a), resistance to drugs (Habets & Brockhurst, 2012) or phages (Brockhurst et al, 2003(Brockhurst et al, , 2005, motility (Brockhurst et al, 2005;Taylor et al, 2015) and loss of social secretions such as siderophores (Brockhurst et al, 2008).…”
mentioning
confidence: 98%